Modelling and dynamical analysis of a DC–DC converter with coupled inductors - D'Amico, María Belén (2019)
The large-signal averaged model of a coupled-inductor double-boost converter is developed and analysed in this paper. Due to the large current fluctuations, the differential system is deduced by averaging the circuit equations of the operation modes over a switching period. Generic expressions that permit to calculate the current commutation intervals as function of the averaged state variables are also found to complete the model. Resistive losses are introduced into an equivalent averaged circuit leading to a more realistic scenario. The proposed state-space model is used for studying voltage conversion ratios, transients and frequency-domain responses of the converter as well as for designing a control loop that regulates the output voltage. Numerical simulations and experimental measurements corroborate the obtained results.